Role of Dietary Micronutrients on Gut Microbial Dysbiosis and Modulation in Inflammatory Bowel Disease. Issue 5 (25th January 2021) - Kundra, Palni; Rachmühl, Carole; Lacroix, Christophe; Geirnaert, Annelies
Abstract: In patients with inflammatory bowel diseases (IBD), dietary micronutrient intake is low and deficiencies are common. Besides the host, also the gut microbiota require micronutrients and low levels may disturb its functioning. Multi‐omics studies indeed detected shifts in micronutrient‐dependent microbial pathways in IBD. It is however not clear whether micronutrients may alleviate inflammation directly, by modulating the immune system, or also indirectly, by modulating the structure and function of the gut microbiota. The latter seems of particular interest, since the gut microbiota is one of the future therapeutic targets in IBD. A review of the most recent available literature on relevant micronutrients in context of IBD and gut microbiota was conducted. An overview per relevant micronutrient on its role on gut bacterial growth, metabolism and host–microbe interactions during gut inflammation is provided. Dietary micronutrients have potential to be part of future personalized microbiome‐targeted therapies in IBD, considering both the micronutrient status of the host and the gut microbiota. However, cohort studies together with integrated multi‐scale studies are needed to understand the mechanisms of micronutrient–microbiome–host interactions in IBD and to evaluate efficacy and safety of dietary micronutrient treatment strategies. Abstract : Low intake of dietary vitamins and minerals by inflammatory bowel disease (IBD) patients may impact the gut microbiota functioning during inflammation, which may further impact IBD pathogenesis. In this review, an overview of relevant micronutrients for IBD, what is known about their role on the gut microbes, their interaction with the gut in IBD, and their therapeutic potential is given.